An International Student Experience Unfolding into Professional Interests (Comparative & International Education Series, 2022)
In 1981, almost forty years ago, I was dreaming of being an international exchange student in the United States. While my father was then very ill, my mother preferred that I did not travel and stayed at home with my family in Rio de Janeiro, Brazil. But both my parents ended up allowing me to pursue this dream because they valued cultural exchanges. I took care of all the bureaucratic endeavours to travel. I would not lose an academic year with an experience of six months, I was determined to study and deeply motivated by the few friends and acquaintances who had been international students. Besides, this was not my first move. As a family, we have not only moved from Brasília to Rio de Janeiro, but also lived in Lebanon, Beirut. Yet, I was the first of a family of five children to travel to the United States.